Analisis Faktor-Faktor Produksi Yang Mempengaruhi Pendapatan Petani Sawit Rakyat Di Desa Sri Tanjung, Kecamatan Rupat, Kabupaten Bengkalis - Siregar, Alhafizy; Harahap, Gustami (Universitas Medan Area, 2025)
The purpose of this study is to see how smallholder oil palm farmers in Sri Tanjung Village, Rupat District, Bengkalis Regency. The validity of this study was confirmed by using quantitative techniques. Around 42 oil palm farmers from Sri Tanjung Village in Rupat District, Bengkalis Regency, became the research sample. After the questionnaire was distributed and validated to determine its reliability and validity, the classical assumptions of heteroscedasticity, multicollinearity, and normality were also examined, then the proposed hypothesis was assessed using SPSS 30 multiple linear regression and the coefficient of determination. This study found that Farmer Capital spent on agricultural tools and equipment increases oil palm productivity, which increases farmer income. It has also been shown that fertilization has a significant impact on improving the quality and quantity of the harvest, with farmers often getting better yields when they use good fertilization procedures. permanent employee labor and family members help maintain the smoothness and efficiency of production, while limited supply of qualified personnel can affect the best results. The results of the study indicate that by using this method, oil palm farmers in Sri Tanjung Village can double their income. The data found that these three parameters had a significant impact on oil palm development and harvest success.